PENGARUH STORE ATMOSPHERE, DISPLAY PRODUCT, DAN PRICE DISCOUNT TERHADAP IMPULSE BUYING (Studi kasus pada Indomaret di kota Denpasar) - Artana, I Putu Widya; Wisesa, I Gusti Bagus Satria; Setiawan, I Komang; Utami, Ni Luh Putu Mita Pramestya; Yasa, Ni Nyoman Kerti; Jatra, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.04.TAHUN 2019, 2019)
This study aims to explain the effect of Store Atmosphere, product display, and Price Discount on Impulse Buying. The sample used was 90 respondents using purposive sampling technique that resided in Denpasar City, and had carried out Impulse Buying. Data were analyzed using regression analysis. The results of this study indicate that Store Atmosphere has a positive and significant effect on Impulse Buying; product display has a significant positive effect on Impulse Buying; and Price Discount has a significant positive effect on Impulse Buying. The implications of this research suggest that Indomaret always develop store atmoshere and product displays to be better, and still provide a Price Discount policy.